2011
DOI: 10.1111/j.1542-474x.2011.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Tachogram Length and Period of Recording during Noninvasive Investigation of the Autonomic Nervous System

Abstract: During application of orthostatic stress the exact starting point of recording, as well as the length of recording, is critical due to the activation and normalization of homeostatic mechanisms. Starting the tachogram recording too late will miss out on part of the initial response to change in body position. Longer recording times will give a combination of values recorded during the stress response and values obtained after stabilization in the standing position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…In the supine position, HR is primarily regulated by parasympathetic influences, while rising and standing trigger the sympathetic branch of the ANS as seen by the increases in HR. A previous study by our group indicated that exercise-induced changes in sympathetic and parasympathetic ANS control differ, depending on posture, that is supine, rising and standing 29. For this reason, the determination of the influence of baseline physiological indicators on exercise-induced changes in HRV measured during rising and standing periods may provide new insights.…”
Section: Resultsmentioning
confidence: 96%
“…In the supine position, HR is primarily regulated by parasympathetic influences, while rising and standing trigger the sympathetic branch of the ANS as seen by the increases in HR. A previous study by our group indicated that exercise-induced changes in sympathetic and parasympathetic ANS control differ, depending on posture, that is supine, rising and standing 29. For this reason, the determination of the influence of baseline physiological indicators on exercise-induced changes in HRV measured during rising and standing periods may provide new insights.…”
Section: Resultsmentioning
confidence: 96%
“…32,33 Statistical analysis was performed using MATLAB ® (Version 2015b, MathWorks). All methods were applied on the single-subject level, and presented on the group-level.…”
Section: Resultsmentioning
confidence: 99%
“…We have in a previous publication showed that HRV indicators already stabilized for the standing position during this period (180 to 360s after rising). 46 No significant exercise-induced changes in pure vagal HR control (RMSSD, pNN50, SD1 and HFms 2 were found). However, in the face of no exerciseinduced change in vagal indicators, the increase in the SD2 indicator of non-linear rhythms and LFnu, showed a pre-post exercise induced increase in the sympathetic response.…”
mentioning
confidence: 88%
“…The orthostatic response is generally seen as the difference between values obtained during the supine period and that obtained in response to the orthostatic stressor . 18,26,43 Complicating factors include uncertainties about the exact tachogram starting point during or after standing-up, the length of recording, which is critical due to the activation and normalisation of homeostatic mechanisms, 46 and the importance of stationarity during HRV measurements. 20 The interpretation of when to record the values in response to the stressor differ.…”
mentioning
confidence: 99%
See 1 more Smart Citation